Experimental Buddhism : Innovation and Activism in Contemporary Japan - Nelson, John K. (John Kenneth), 1953- (Book collections on Project MUSE., 2014)
This work documents a sense of what is happening on the front lines as a growing number of Buddhist priests try to reboot their roles and traditions to gain greater significance in Japanese society. It profiles innovative as well as controversial responses to the challenges facing Buddhist priests.